2014
DOI: 10.1186/bf03353085
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake cycles and physical modeling of the process leading up to a large earthquake

Abstract: A thorough discussion is made on what the rational constitutive law for earthquake ruptures ought to be from the standpoint of the physics of rock friction and fracture on the basis of solid facts observed in the laboratory. From this standpoint, it is concluded that the constitutive law should be a slip-dependent law with parameters that may depend on slip rate or time. With the long-term goal of establishing a rational methodology of forecasting large earthquakes, the entire process of one cycle for a typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 101 publications
1
27
0
Order By: Relevance
“…doi:10.5047/eps.2012.04.006 et al, 1993;Ohnaka, 2004;Oishi and Sato, 2007). However, some studies have obtained weak interplate coupling (20-40%) (Peterson and Seno, 1984;Pacheco et al, 1993;Matsumoto et al, 2008), whereas others have shown strong coupling along the Japan Trench (Nishimura et al, 2004;Suwa et al, 2006;Hashimoto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…doi:10.5047/eps.2012.04.006 et al, 1993;Ohnaka, 2004;Oishi and Sato, 2007). However, some studies have obtained weak interplate coupling (20-40%) (Peterson and Seno, 1984;Pacheco et al, 1993;Matsumoto et al, 2008), whereas others have shown strong coupling along the Japan Trench (Nishimura et al, 2004;Suwa et al, 2006;Hashimoto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent comment by Bizzarri and Cocco (2006) represents their counterargument to this remark. The basis of their reasoning is that even if the +1 term was included in the argument of the logarithm in equations (1c) and (1d) described in the paper (Ohnaka, 2004), the traction dependence on slip rate would remain in the governing equation, because the state variable depends on the fault slip velocity (Bizzarri and Cocco, 2006). I feel the need to point out, however, that their counterargument still appears to be logically inconsistent.…”
mentioning
confidence: 99%
“…In response to Cocco and Bizzarri's (2002) argument that "there is no need to assume that friction must become independent of slip rate at high speeds to resemble slip weakening", I remarked in my previous paper (Ohnaka, 2004) that "this argument seems logically inconsistent, because the effect of high velocity cutoff has been incorporated into the equation used in their simulation." The most recent comment by Bizzarri and Cocco (2006) represents their counterargument to this remark.…”
mentioning
confidence: 99%
See 2 more Smart Citations